The loss-of-function mutation of CETP affects HDLc levels but not ApoA1 in patients with acute myocardial infarction - Li, Weiping; Liu, Xin; Huang, Chunyi; Liu, Liusheng; Tan, Xuerui; Wang, Xingyu (Nutrition, metabolism, and cardiovascular diseases, 2021)
Loss of the cholesteryl ester transfer protein (CETP) function affects HDLc levels, but its effects on major HDL protein component ApoA1 are not well understood in patients with acute myocardial infarction (AMI). We investigated the effects of an East Asian loss-of-function variant (rs2303790; p.D442G) in CETP gene on HDLc and ApoA1 levels and its relationship with AMI. A total of 2327 AMI patients and 2615 age- and sex-matched controls from INTERHEART-China study were included. In controls, both levels of HDLc (1.24 vs. 1.04 mmol/L, P = 0.001) and ApoA1 (1.48 vs. 1.37 mmol/L, P = 0.042) were significantly higher in CETP variant G allele carriers compared to CETP wildtype D allele carriers. In AMI patients, levels of HDLc were significantly higher (1.14 vs. 1.01 mmol/L, P = 0.013) while levels of ApoA1 were not statistically difference (1.31 vs. 1.32 mmol/L, P = 0.468) in CETP variant group compared to CETP wildtype group. Moreover, CETP variant is associated with HDLc increase, but is not associated with AMI risk (P = 0.564), even after adjusting for age, sex, history of hypertension and diabetes, waist to hip ratio, smoking, total cholesterol, LDL cholesterol, triglycerides, physical activity, depression, alcohol, vegetables and fruit consumption. Loss of CETP function is associated with increased HDLc and ApoA1 levels in healthy subjects, and in AMI patients, it is associated with HDLc levels but not ApoA1 levels. The lack of association of CETP variant with AMI may be related to the inability to increase ApoA1 levels and warranted further studies. •CETP functional mutation affects HDL levels in both AMI patients and controls.•CETP functional mutation affects ApoA1 levels in controls, but not in AMI patients.•CETP functional mutation has no association with AMI risk.